Determinants of Heterosexual Men S Attitudes Toward Gay Men and Lesbians in Chile - Barrientos-Delgado, J (Routledge, 2018)
We studied the effects of different sets of sociopolitical variables on attitudes toward gay men and lesbians in a Chilean sample of heterosexual men (n = 121). Based on these data, a hierarchical linear regression was performed, with the dependent variable being attitudes toward gay men and lesbians. Results reveal the importance of two variables, authoritarian aggression and gender role beliefs, which are relevant for both gay men (β =.27 and β =.44, respectively) and lesbian (β =.30 and β =.36, respectively) assessment. The only difference in the assessment of both groups is that conventionalism (β =.22) is relevant for evaluating gay men, while for lesbians the relevant variable is authoritarian submission (β =.22). These results are important because they indicate that heterosexual men make a differential assessment on the basis of two variables: adhesion to dominant values (being a fundamental dimension in the case of gay men) and degree of submission or attachment to an alleged legitimate authority which ends up in keeping them in an inferior condition (fundamental in the case of lesbians). When these values and social hierarchy are questioned, the level of negative attitudes may be more evident. © 2018 The Author(s). Published with license by Taylor & Francis Group, LLC. © 2018 Manuel Cárdenas, Jaime Barrientos, and Fabiola Gómez.